High‐Performance and Industrially Viable Nanostructured SiOx Layers for Interface Passivation in Thin Film Solar Cells. Issue 3 (27th January 2021) - Cunha, José M. V.; Oliveira, Kevin; Lontchi, Jackson; Lopes, Tomás S.; Curado, Marco A.; Barbosa, João R. S.; Vinhais, Carlos; Chen, Wei-Chao; Borme, Jérôme; Fonseca, Helder; Gaspar, João; Flandre, Denis; et al.
Abstract : Herein, it is demonstrated, by using industrial techniques, that a passivation layer with nanocontacts based on silicon oxide (SiO x ) leads to significant improvements in the optoelectronical performance of ultrathin Cu(In, Ga)Se2 (CIGS) solar cells. Two approaches are applied for contact patterning of the passivation layer: point contacts and line contacts. For two CIGS growth conditions, 550 and 500 °C, the SiO x passivation layer demonstrates positive passivation properties, which are supported by electrical simulations. Such positive effects lead to an increase in the light to power conversion efficiency value of 2.6% (absolute value) for passivated devices compared with a nonpassivated reference device. Strikingly, both passivation architectures present similar efficiency values. However, there is a trade‐off between passivation effect and charge extraction, as demonstrated by the trade‐off between open‐circuit voltage ( V oc ) and short‐circuit current density ( J sc ) compared with fill factor (FF). For the first time, a fully industrial upscalable process combining SiO x as rear passivation layer deposited by chemical vapor deposition, with photolithography for line contacts, yields promising results toward high‐performance and low‐cost ultrathin CIGS solar cells with champion devices reaching efficiency values of 12%, demonstrating the potential of SiO x as a passivation material for energy conversion devices. Abstract : Two SiO x passivation architectures are applied in ultrathin Cu(In, Ga)Se2 (CIGS) solar cells. Both passivation approaches result in devices with higher performance compared with a reference nonpassivated device. The potential to use SiO x as passivation material, deposited by a high throughput industrial technique based on microelectronics processing, yields promising results toward high‐performance low‐cost ultrathin CIGS solar cells for energy conversion.